1985
DOI: 10.1111/j.1365-3024.1985.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of immunity to Nematospiroides dubius: a 9‐day anthelmintic abbreviated immunizing regime which separates weak and strong responder strains of mice

Abstract: Behnke, Jerzy M. and Robinson, M. (1985) Genetic control of immunity to Nematospiroides dubius: a 9-day anthelmintic abbreviated immunizing regime which separates weak and strong responder strains of mice. A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 23 publications
4
95
0
Order By: Relevance
“…The study reported in this paper was necessary to provide us with data on optimal doses of ivermectin. The adult stages of H. polygyrus are immunosuppressive in the mouse (Behnke, 1987 ) whilst the larval stages provide the antigenic stimulus, which in responder strains results in the development of acquired immunity (Jacobson et al, 1982;Behnke and Robinson, 1985). The larvae of H. polygyrus develop for 8-10 days in the muscularis externa and undergo a moult during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported in this paper was necessary to provide us with data on optimal doses of ivermectin. The adult stages of H. polygyrus are immunosuppressive in the mouse (Behnke, 1987 ) whilst the larval stages provide the antigenic stimulus, which in responder strains results in the development of acquired immunity (Jacobson et al, 1982;Behnke and Robinson, 1985). The larvae of H. polygyrus develop for 8-10 days in the muscularis externa and undergo a moult during this period.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue stages of H. polygyrus (1-8 days post infection) are hardly affected by pyrantel and the drug cannot be used to terminate infections earlier than 10-14 days post infection (Behnke and Wakelin, 1977;Behnke and Robinson, 1985 ). Nevertheless, there is evidence that the earlier stages are immunogenic, particularly L4 and hence there is a requirement for drugs that show high efficacy against the tissue-dwelling larval stages ofH.…”
Section: Introductionmentioning
confidence: 99%
“…The first inbred strain to show an unusually high level of resistance to challenge was a little-known strain called NIH (Behnke and Wakelin, 1977), but even this strain was not able to remove primary infection adult worms easily (Behnke and Robinson, 1985). Cypess et al (1977) reported on a hybrid strain (LAF1) able to clear up to 50 % of adult worms by 3 weeks after infection, and Prowse et al (1979) and Mitchell et al (1982) identified the inbred SJL strain as one that removes adult worm infections rapidly, in contrast to other mouse strains.…”
Section: G E N E T I C S O F T H E H O S T R E S P O N S E T O C H R mentioning
confidence: 99%
“…Most helminth parasites are long-lived and, in general, cause chronic infections (3,30). However, the immune mechanism(s) underlying the chronicity of helminth infection is not fully understood.…”
Section: Vol 73 2005 Modulation Of Antimalarial Immunity By Nematodmentioning
confidence: 99%
“…H. polygyrus is a murine nematode parasite that dwells in the small intestine of the host. In most inbred strains of mice, H. polygyrus establishes a chronic primary infection, which lasts for several months (3,30). Infection with this nematode parasite induces a strong Th2 immune response characterized by production of the cytokines interleukin-4 (IL-4), IL-5, and IL-13, immunoglobulin E (IgE) and IgG1 antibodies, eosinophilia, and mastocytosis in intestinal mucosal tissue (14,15,20,22).…”
mentioning
confidence: 99%